Tracking the dynamics of skyglow with differential photometry using a digital camera with fisheye lens. (April 2018) - Jechow, Andreas; Ribas, Salvador J.; Domingo, Ramon Canal; Hölker, Franz; Kolláth, Zoltán; Kyba, Christopher C.M.
Abstract : Highlights: Investigating the dynamics of skyglow from time series of images. Observing the impact of switching off ornamental light sources on skyglow for clear and overcast sky. Imaging in vertical and horizontal plane with fisheye lens and DSLR camera. Tracking small changes in luminance of the sky, the ground and light sources simultaneously. Method is based on readily available consumer equipment. Abstract: Artificial skyglow is dynamic due to changing atmospheric conditions and the switching on and off of artificial lights throughout the night. Street lights as well as the ornamental illumination of historical sites and buildings are sometimes switched off at a certain time to save energy. Ornamental lights in particular are often directed upwards, and can therefore have a major contribution towards brightening of the night sky. Here we use differential photometry to investigate the change in night sky brightness and illuminance during an automated regular switch-off of ornamental light in the town of Balaguer and an organized switch-off of all public lights in the village of Àger, both near Montsec Astronomical Park in Spain. The sites were observed during two nights with clear and cloudy conditions using a DSLR camera and a fisheye lens. A time series of images makes it possible to track changes in lighting conditions and sky brightness simultaneously. During the clear night, the ornamental lights in Balaguer contribute over 20% of the skyglow at zenith at the observational site. Furthermore, we are able to track very small changes in the ground illuminance on a cloudy night near Àger.